(untitled) (Journal of Population and Development, 2021)
Diversity, natural resources and indigenous knowledge are the wealth of Nepal. Nepalese indigenous people possesses large varieties in language, culture, traditions, art and literatures which can also be applied as knowledge system and can also be taken as indigenous knowledge. These indigenous knowledge are applicable not only in the continuation of beliefs, customs and traditions but also helpful in conservation of natural resources and environment. This paper aims to uncover the application of indigenous knowledge of some groups of indigenous people of Nepal and has applied descriptive and interpretive methods of study. The nature of data used in the study is qualitative. Most of practices are culturally and religiously important which are directly and indirectly helpful in environmental conservation but there is need of further scientific investigation and verification also.